Reproductive Performance, Retention Rate, and Age at the Third Parity According to Growth Rate and Age at First Mating in the Gilts with a Modern Genotype - Faccin, Jamil Elias Ghiggi; Laskoski, Fernanda; Lesskiu, Paulo Emílio; Paschoal, Aline Fernanda Lopes; Mallmann, André Luiz; Bernardi, Mari Lourdes; Mellagi, Ana Paula Gonçalves; Wentz, Ivo; Bortolozzo, Fernando Pandolfo (Acta Scientiae Veterinariae, 2017)
Background: Gilts represent the largest category (18-20%) of female pigs in a breeding herd. Under field conditions, the amplitude of growth rate and age at the first mating of gilts are remarkably higher than the recommendations made by the genetic companies. There are several studies that have considered the management of these animals starting from their introduction to the herd till the mating. It has been noted that the genetic selection constantly promotes evolution that may change certain traits of these animals. However, there is a lack of the studies that evaluate the management strategies suitable for the modern sows. This study, therefore, aimed to evaluate the effect of age and growth rate of gilts at the first mating on productive performance and retention rate until the third farrowing. Materials, Methods & Results: The study was performed in a gilt development unit (GDU) with a breeding stock capacity of 1000 females and a goal of 90 gilts mating per week. The groups were retrospectively created according to age (<210 d and ≥210 d) and the growth rate (GR; <700 g/d and ≥700 g/d) at the first mating with a 2 × 2 factorial design. A real-time ultrasound examination was performed at approximately 28 days after artificial insemination to detect pregnancy. Afterward, the productivity data over three parities of 703 females were collected and analyzed at 28 commercial farms of destination. The analyses were performed using SAS, with individual gilts as the experimental unit. The total number of piglets born and the age at the third parity were analyzed using the PROC MIXED. The number of estrus at breeding, weaning-to-estrus interval and the number of piglets in the previous farrowing were included as covariates in the model of total piglets born. The farrowing rate and retention rate until the third parity were considered as binary responses and analyzed using logistic regression (PROC GLIMMIX). The effects of age, GR, and their interaction were included as fixed effect in all analyses. There was no effect of age and GR and their interaction (P > 0.05) on farrowing rate after first, second, and third mating. The total number of piglets born in the three first farrowing and over three parities were not affected (P > 0.05) by the age and GR at first mating. The retention rate until the third farrowing of gilts inseminated with more than 210 days of age was approximately 7% greater than in the gilts mated younger; however, no statistical difference (P > 0.05) was detected. An effect of the age at the first mating was observed in the age to reach the third farrowing. Gilts mated with less than 210 and more than 210 days reached the third farrowing, respectively, at 604.5 ±1.9 and 625.1 ± 2.7 days of age (P < 0.001). Discussion: With a minimum GR of 550 g/d, 180 days of age, and at least 130 kg of weight, gilts are eligible to be inseminated without impairing their litter size, farrowing, and retention rate until the third parity. The gilts having modern genotypes can have a high stillbirth rate if bred with an excessive body weight. It is worth to consider that the gilts inseminated with > 700g/d did not present overweight in this study. The reproductive performance expressed by farrowing rate and piglets born and the longevity expressed by the retention rate from the first pregnancy until the third parturition were not impaired by the groups of age and GR in Large White × Landrace crossbred (Camborough 23®). In addition, gilts inseminated earlier than 210 days but having the minimum required weight resulted in less non-productive days for the breeding herd, which represents an important financial rate to the system.